Diagnosis of glutaric aciduria type 1 by measuring 3-hydroxyglutaric acid in dried urine spots by liquid chromatography tandem mass spectrometry - Al-Dirbashi, Osama Y.; Kölker, Stefan; Ng, Dione; Fisher, Lawrence; Rupar, Tony; Lepage, Nathalie; Rashed, Mohamed S.; Santa, Tomofumi; Goodman, Stephen I.; Geraghty, Michael T.; Zschocke, Johannes; Christensen, Ernst; et al. (Journal of inherited metabolic disease, 2011)
Accumulation of glutaric acid (GA) and 3-hydroxyglutaric acid (3HGA) in body fluids is the biochemical hallmark of type 1 glutaric aciduria (GA1), a disorder characterized by acute striatal degeneration and a subsequent dystonia. To date, methods for quantification of 3HGA are mainly based on stable isotope dilution gas chromatography mass spectrometry (GC-MS) and require extensive sample preparation. Here we describe a simple liquid chromatography tandem MS (LC-MS/MS) method to quantify this important metabolite in dried urine spots (DUS). This method is based on derivatization with 4-[2-(N,N-dimethylamino)ethylaminosulfonyl]-7-(2-aminoethylamino)-2,1,3-benzoxadiazole (DAABD-AE). Derivatization was adopted to improve the chromatographic and mass spectrometric properties of the studied analytes. Derivatization was performed directly on a 3.2-mm disc of DUS as a sample without extraction. Sample mixture was heated at 60°C for 45 min, and 5 μl of the reaction solution was analyzed by LC-MS/MS. Reference ranges obtained were in excellent agreement with the literature. The method was applied retrospectively for the analysis of DUS samples from established low- and high-excreter GA1 patients as well as controls (n = 100). Comparison of results obtained versus those obtained by GC-MS was satisfactory (n = 14). In populations with a high risk of GA1, this approach will be useful as a primary screening method for high- or low-excreter variants. In these populations, however, DUS analysis should not be implemented before completing a parallel comparative study with the standard screening method (i.e., molecular testing). In addition, follow-up DUS GA and 3HGA testing of babies with elevated dried blood spot C5DC acylcarnitines will be useful as a first-tier diagnostic test, thus reducing the number of cases requiring enzymatic and molecular analyses to establish or refute the diagnosis of GA1.